Ultra-fast highly sensitive flexible infrared detector - A.R. Rymzhina; P. Sharma; V.V. Podlipnov; D.N. Artemyev; K.N. Tukmakov; V.S. Pavelyev; V.I. Platonov; P. Mishra; N. Tripathi (Компьютерная оптика)
A comparative analysis of photodetectors based on TiS2 nanosheets and on TiS2 nanosheets functionalized with silver nitrate is carried out. TiS2 nanosheets were synthesized by a chemical vapor transport technique, followed by a 1-hour ultrasonication treatment. The obtained solution was deposited between interdigitated electrodes fabricated on the surface of a flexible substrate using a dielectrophoresis process. Polyethylene terephthalate was used as a flexible substrate material. The characteristics of the fabricated photodetectors were determined by illuminating them with tunable-power laser light at 1064 nm. A significant effect of silver nitrate particles scattered in the volume of the photodetector sensitive material on its efficiency is observed. The superiority of the photodetector based on TiS2 nanosheets functionalized with silver nitrate is demonstrated. This photodetector demonstrates a significant response for all the laser light powers used (11.6, 19.6, 51, 100, and 150 mW), shows fast response (0.23±0.01 s) and recovery (0.49±0.02 s) times, coupled with high sensitivity (260∙103±7∙103 A/W), quantum efficiency (303∙103±8∙103 A/W∙nm) and detectivity (3.10∙1013±0.09∙1013 Jones) at an incident laser light power of 11.6 mW. The results obtained in this study can be used for the development and optimization of modern optoelectronic devices.